2021
DOI: 10.1053/j.gastro.2021.02.020
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Community Heterogeneity Within Colorectal Neoplasia and its Correlation With Colorectal Carcinogenesis

Abstract: Author names in bold designate shared co-first authorship.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
81
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(83 citation statements)
references
References 32 publications
2
81
0
Order By: Relevance
“…(3) Patients with metastasis or recurrence have more intratumoral F. nucleatum than patients without metastasis or recurrence ( Chen Y. et al, 2020 ; Yu et al, 2017 ). (4) Even in the same tumor tissues, the abundance of F. nucleatum varies at different sampling sites ( Liu W. et al, 2021 ).…”
Section: F Nucleatum and Crc: Clinical Studies In Different Sample Typesmentioning
confidence: 99%
“…(3) Patients with metastasis or recurrence have more intratumoral F. nucleatum than patients without metastasis or recurrence ( Chen Y. et al, 2020 ; Yu et al, 2017 ). (4) Even in the same tumor tissues, the abundance of F. nucleatum varies at different sampling sites ( Liu W. et al, 2021 ).…”
Section: F Nucleatum and Crc: Clinical Studies In Different Sample Typesmentioning
confidence: 99%
“…In this study, we found that the abundance of Fusobacterium nucleatum increased in the test group, and this increase is possibly related to terminal ileal NLH. Fusobacterium nucleatum has been reported to be enriched in colorectal cancer tissues and played a crucial role in the occurrence and development of colorectal cancer[ 32 ]. It can adhere to and invade intestinal epithelial cells and activate the β-catenin pathway by releasing FadA adhesin and binding with cadherin E-cadherin, thus promoting inflammation and tumor response[ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…The exact nature of how colibactin production may alter transcriptional regulation or abundance of gut microbes is not well understood. However, the relevance of microbial dysbiosis in the etiology of various cancers is well-defined [70][71][72]. Future studies focusing on how colibactin influences multi-kingdom interactions in the gut may elucidate novel pathways by which pks + bacterial colonization deleteriously affects their host.…”
Section: Modulation Of Tumor Microenvironmentmentioning
confidence: 99%